2023
DOI: 10.3390/v15081637
|View full text |Cite
|
Sign up to set email alerts
|

The Stereotypic Response of the Pulmonary Vasculature to Respiratory Viral Infections: Findings in Mouse Models of SARS-CoV-2, Influenza A and Gammaherpesvirus Infections

Abstract: The respiratory system is the main target of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of coronavirus disease 19 (COVID-19) where acute respiratory distress syndrome is considered the leading cause of death. Changes in pulmonary blood vessels, among which an endothelialitis/endotheliitis has been particularly emphasized, have been suggested to play a central role in the development of acute lung injury. Similar vascular changes are also observed in animal models of COVID-19. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…To investigate the frequency of genomic changes that occur in SARS-CoV-2 in the immune compromised or competent host in the presence or absence of antiviral drugs, K18-hACE2 transgenic mice were used as a model for severe SARS-CoV-2 infection in humans 44 . We have found that the pathological changes in the lungs in this model in many aspects resemble those in humans who have died of severe COVID-19 26,28,29,32,33 . To mimic a host with compromised immunity, an experimental protocol was developed in which mice were exposed to cyclophosphamide 40 (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…To investigate the frequency of genomic changes that occur in SARS-CoV-2 in the immune compromised or competent host in the presence or absence of antiviral drugs, K18-hACE2 transgenic mice were used as a model for severe SARS-CoV-2 infection in humans 44 . We have found that the pathological changes in the lungs in this model in many aspects resemble those in humans who have died of severe COVID-19 26,28,29,32,33 . To mimic a host with compromised immunity, an experimental protocol was developed in which mice were exposed to cyclophosphamide 40 (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Consecutive sections (3-5 µm) were either stained with hematoxylin and eosin (HE) or used for immunohistology (IH). IH was performed to detect viral antigen expression using the horseradish peroxidase method and a rabbit anti-SARS-CoV nucleocapsid protein (Rockland, 200-402-A50) as primary antibody, as previously described 26, 32, 33 .…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of infected cells in the lung at 4dpi was low and this may reflect the semi-permissive nature of hRSV infection of mice (reviewed in 83 ). Despite the low frequency of infection, RSV induced a similar inflammatory response as seen with other respiratory viruses, such as SARS-CoV-2 and IAV, with clear evidence of leukocyte recruitment and monocyte and T cell driven vasculitis and perivascular/peribronchial infiltration 84 . Daprodustat treatment dampened these inflammatory responses, although the recruitment of neutrophils was maintained, in line with earlier reports on hypoxia driving neutrophilic inflammation 85 .…”
Section: Discussionmentioning
confidence: 80%
“…A formalin fixed and paraffin embedded RSV infected (MOI 0.2, 48 hpi) Calu-3 pellet served as positive control; tissue sections incubated without the primary antibody served as negative controls. Further sections were stained for Iba1 (monocytes/macrophage marker), CD3 (T cell marker) and Ly6G (neutrophil marker) following previously published protocols 84,88 .…”
Section: Methodsmentioning
confidence: 99%
“…The pathology of LRT infection by SARS-CoV-2, and the consequent severe disease that requires hospital treatment, is complex and involves a central role for dysfunctional immune responses [12,13]. SARS-CoV-2 infection of the lungs can lead to uncontrolled coagulation and inflammation in the lungs, increased permeability of vascular endothelium [15], diffuse alveolar damage where the lungs are unable to maintain adequate oxygen supply, and systemic pathology [12,13]. The primary goal of COVID-19 vaccination to date has been to prevent or minimize the development of severe disease and death, which is closely dependent on averting or rapidly eliminating SARS-CoV-2 infections in the URT.…”
Section: Introductionmentioning
confidence: 99%